2020
DOI: 10.1021/acs.jafc.9b07443
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Spermidine Synthase Gene from Soybean by Recombinant Expression, Transcriptional Verification, and Sequence Analysis

Abstract: Spermidine possesses multiple healthy functions, and soybeans contain the most abundant spermidine. In this study, spermidine contents of soybeans from different varieties and production regions in China were evaluated, and a spermidine synthase gene (speE) was identified by recombinant expression, transcriptional verification, and sequence analysis. Spermidine contents of soybean samples from 18 varieties ranged 72.38–228.82 mg/kg, and those from 19 production regions ranged 134.64–242.32 mg/kg. The highest-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 27 publications
0
21
0
Order By: Relevance
“…In particular, the content of spermidine in raw soybeans ranges from 72 to 242 mg/kg (Glória et al, 2005;Nishibori et al, 2007;Pavel & Petra, 2005;Zou et al, 2020). Plant varieties as well as the planting conditions affect the spermidine contents in food materials (Plonka & Michalski, 2016).…”
Section: Plant Sources Of Spermidinementioning
confidence: 99%
See 3 more Smart Citations
“…In particular, the content of spermidine in raw soybeans ranges from 72 to 242 mg/kg (Glória et al, 2005;Nishibori et al, 2007;Pavel & Petra, 2005;Zou et al, 2020). Plant varieties as well as the planting conditions affect the spermidine contents in food materials (Plonka & Michalski, 2016).…”
Section: Plant Sources Of Spermidinementioning
confidence: 99%
“…Plant varieties as well as the planting conditions affect the spermidine contents in food materials (Plonka & Michalski, 2016). Zou et al have revealed that the spermidine content of different soybean variety is significantly different (Zou et al, 2020). Sagara et al have also proved that soybean genotypes and planting conditions had substantial effects on spermidine content (Sagara et al, 2017).…”
Section: Plant Sources Of Spermidinementioning
confidence: 99%
See 2 more Smart Citations
“…Spermidine synthase catalyzes the transfer of the aminopropyl group from dcSAM to putrescine to form the spermidine [29], which is considered to be a rate-limiting step in biosynthesis of spermidine [30]. It is particularly essential to exploit e cient spermidine synthase genes (speE).…”
Section: Effects Of Different Spermidine Synthase Genes On Spermidinementioning
confidence: 99%